2015
DOI: 10.1016/j.fsigss.2015.09.237
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA from fingernail samples in criminal cases

Abstract: The detection of foreign DNA from the fingernail hyponychium may be relevant in the investigation of certain criminal acts, providing evidence of any sort of contact between the victim and the suspect.In this report, we analyzed results obtained from 164 fingernail samples collected by three different methods: extraction, clipping and swabbing. Samples were taken, mostly during the autopsy operation, and submitted to our Lab in the context of 71 different criminal cases.In 74.6% of the reviewed cases, a report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…It is well established that foreign DNA can accumulate under an individual's fingernails [70,[146][147][148][149][150][151][152][153][154][155][156][157][158][159], and this knowledge has been considered further in respect to its use in investigating crimes [39,42]. This DNA is relatively protected compared to other parts of the body that are exposed to physical contacts and actions.…”
Section: Fingernail Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that foreign DNA can accumulate under an individual's fingernails [70,[146][147][148][149][150][151][152][153][154][155][156][157][158][159], and this knowledge has been considered further in respect to its use in investigating crimes [39,42]. This DNA is relatively protected compared to other parts of the body that are exposed to physical contacts and actions.…”
Section: Fingernail Samplesmentioning
confidence: 99%
“…However, in approximately 31% of all couples, no male DNA was detected after scratching, thus highlighting that a negative result does not necessarily indicate that scratching did not take place. -Casework fingernail samples: A number of casework sample studies (including homicides and sex offences) reported mixed DNA profiles in the range of 13 to 35% of samples (n=over 300 cases); however, 'higher quality' mixtures were detected in 7-21% of these [148,149,153,[156][157][158]. In several instances, the foreign component was detected as the major contributor.…”
Section: Examples Of Various Studies Includementioning
confidence: 99%
“…Violent crimes are often associated with intense physical contact between the victim and the perpetrator due to struggling at the scene of the crime. This facilitates the transference of blood, epithelial cells, semen, or any other biological material between the two individuals, which could collect under the suspect's or the victim’s fingernails [ 11 , 12 ]. Thus, finding foreign biological material under the fingernails of the cadaver can be valuable evidence in the investigation of a homicide.…”
Section: Discussionmentioning
confidence: 99%
“…In controlled experiments with females scratching males to simulate assaults, 95% (38 out of 4288 40) of fingernail samples collected immediately and 60% (24 out of 40) of those collected 4289 five hours later were "suitable for comparison" (Iuvaro et al 2018). Analyses of fingernail 4290 samples in criminal cases were also studied (Bozzo et al 2015). 4291 4292…”
Section: Digital Penetrationmentioning
confidence: 99%